"Piezosurgery vs bur in impacted mandibular third molar surgery: Evaluation of postoperative sequelae" - Chirag Patil; Anendd Jadhav; Rajanikanth K; Nitin Bhola; Rajiv M. Borle; Apoorva Mishra (Elsevier, 2019)
Abstract-: Purpose: Piezosurgery is a relatively novel, precise and safe technique of ostectomy in the domain of oral and maxillofacial surgery. Our aim was to compare the inflammatory outcomes of osteotomy using piezosurgery and conventional bur in impacted mandibular third molar (IM3M) surgery. Subjects and method: The study implemented a randomized, double-blind, crossover design. 120 sides in 60 patients were randomly allocated to the two interventions used, viz; conventional bur and piezosurgery. The primary outcome variables evaluated were facial swelling, trismus, pain, and paresthesia. Additionally, the duration of surgery and the frequency of soft tissue injuries with the use of two techniques were also evaluated. Results: Pain, swelling, trismus, and soft tissue injuries emerged to be significantly higher with the use of bur as compared to the piezo. The duration of surgery was significantly extended in the piezo group and no significant difference was observed in the occurrence of paresthesia between the two groups. Conclusion: The result suggests that piezosurgical osteotomy technique is superior to conventional bur in terms of the postoperative inflammatory outcomes in IM3M surgery.